PENENTUAN HARGA JUAL DALAM PERSPEKTIF TAFSIR LABA PADA PETERNAK AYAM JAGO DI DESA MADENAN (Studi Kasus pada Peternak Ayam Jago di Desa Madenan, Kabupaten Buleleng): (Studi Kasus pada Peternak Ayam Jago di Desa Madenan, Kabupaten Buleleng) - Komang Yogiswara; Luh Gede Kusuma Dewi (Universitas Pendidikan Ganesha, 2022)
This study aims to determine the price of madenan studs and brooders by rooster breeders in Madenan Village, to find out the treatment of Madenan roosters by rooster breeders in Madenan Village, to find out how to determine the selling price of Madenan roosters, to find out how the rooster breeders in Madenan Village in interpreting the profits earned on Madenan roosters. This research uses descriptive qualitative method. The data collection technique is by conducting observations, interviews, and documentation which will be processed through analysis based on the observations and knowledge of the researcher. The results of the study showed that (1) the purchase price of roosters and roosters in Madenan Village based on the fighting style of chickens and brooders of good breeds, (2) Accounting Treatment of Biological Assets on Madenan Rooster Breeders and performing depletion calculations using the total production method , (3) The selling price of Jaco do Madenan chicken can be seen from the production cost, fighting style, body posture, breed (soroh) of Madenan chicken, (4) Interpretation of Profits Obtained by Rooster Breeders in Madenan Village, namely the profit of inner satisfaction, real profit, and money profit.